β-xylosidase from Selenomonas ruminantium: Immobilization, stabilization, and application for xylooligosaccharide hydrolysis - Terrasan, César Rafael Fanchini; Aragon, Caio Casale; Masui, Douglas Chodi; Pessela, Benevides Costa; Fernandez-Lorente, Gloria; Carmona, Eleonora Cano [UNESP]; Guisan, Jose Manuel (Taylor & Francis, 2016)
The tetrameric β-xylosidase from Selenomonas ruminantium is very stable in alkaline pH allowing it to easily immobilize by multipoint covalent attachments on highly activated glyoxyl agarose gels. Initial immobilization resulted only in slight stabilization in relation to the free enzyme, since involvement of all subunits was not achieved. Coating the catalyst with aldehyde-dextran or polyethylenimine, fully stabilized the quaternary structure of the enzyme rendering much more stabilization to the biocatalyst. The catalyst coated with polyethylenimine of molecular weight 1300 is the most stable one exhibiting an interesting half-life of more than 10 days at pH 5.0 and 50 °C, being, therefore, 240-fold more stable than free enzyme. Optimum activity was observed in the pH range 4.0–6.0 and at 55 °C. The catalyst retained its side activity against p-nitrophenyl α-l-arabinofuranoside and it was inhibited by xylose and glucose. Kinetic parameters with p-nitrophenyl β-d-xylopyranoside as substrate were Vmax 0.20 μmol.min−1 mg prot.−1, Km 0.45 mM, Kcat 0.82 s−1, and Kcat/Km 1.82 s−1 mM−1. Xylose release was observed from the hydrolysis of xylooligosaccharides with a decrease in the rate of xylose release by increasing substrate chain-length. Due to the high thermostability and the complete stability after five reuse cycles, the applicability of this biocatalyst in biotechnological processes, such as for the degradation of lignocellulosic biomass, is highly increased.
Keywords: enzyme immobilization; enzyme stabilization; Selenomonas ruminantium; xylooligosaccharide hydrolysis; β-xylosidase